Promoting Inclusive Organizational Culture through Community Engagement and Diversity Training in Indian IT Companies - Bussa Siva Chaithanya; Savitha Gayathri (Help: Journal of Community Service, 2026)
Building an inclusive organizational culture has become increasingly important in Indian IT companies due to growing workforce diversity and the need to foster equitable participation in workplace communities. Despite the widespread adoption of diversity and inclusion (D&I) policies, many organizations continue to face challenges in translating formal commitments into meaningful inclusive practices. This community service initiative aimed to strengthen employees’ awareness, participation, and commitment to inclusive workplace culture through community engagement and diversity training activities. The program employed a Community-Based Research (CBR) approach involving 200 employees from IT companies in Hyderabad, India. Participants were actively engaged in identifying inclusion challenges, sharing workplace experiences, and co-developing practical solutions. The intervention consisted of needs assessments, diversity awareness training, collaborative discussions, peer-learning activities, and participatory reflection sessions. Data were collected through questionnaires, observations, and participant feedback and analyzed using descriptive statistics and thematic analysis. The findings revealed that the program significantly improved diversity and inclusion awareness, with 58% of participants reporting high or very high awareness of D&I initiatives and 66% demonstrating familiarity with organizational policies. Furthermore, 73% reported a strong sense of belonging, 74% perceived equal opportunities for professional growth, and 77% expressed satisfaction with organizational D&I initiatives. However, participants also identified structural challenges, including uncertainty regarding organizational responsiveness to microaggressions (30%) and the limited availability of long-term inclusion mechanisms such as mentoring programs and employee resource groups. Community engagement and diversity training effectively enhanced awareness, participation, and inclusion within workplace communities.